A Fifteen-year Review of Lymphomas in a Nigerian Tertiary Healthcare Centre - Oluwasola, A Olayiwola; Olaniyi, John A; Otegbayo, Jesse A; Ogun, Gabriel O; Akingbola, Titi S; Ukah, Cornelius O; Akang, Effiong EU; Aken'Ova, Yetunde A (Journal of Health, Population and Nutrition, 2011)
In Africa, epidemiological data on the effect of the HIV epidemic on the occurrence of lymphomas are scanty. The 1990s witnessed the alarming rates of HIV/AIDS in Nigeria. The prevalence of HIV/AIDS in Nigeria increased from 1.8% in 1991 to 4.4% in 2005. The aim of this study was to determine whether there have been any changes in the frequency and pattern of lymphomas in view of the HIV/AIDS epidemic in the country. This is a retrospective study of all lymphoma cases diagnosed during 1991-2005. The prevalence of lymphomas declined from 1.4% to 0.7% of surgical biopsies during 1991-2005. There was a decline in the proportion of high-grade non-Hodgkin lymphoma and Burkitt’s lymphoma from 79.1% and 45.8% respectively to 21.1% and 13.6% respectively. There is a suggestion that the HIV/AIDS epidemic in the country may not have influenced the pattern of occurrence of both major histomorphological types of lymphoma in Ibadan. Key words: Acquired immunodeficiency syndrome; HIV; Lymphomas; Retrospective studies; Africa DOI: http://dx.doi.org/10.3329/jhpn.v29i4.8446 JHPN 2011; 29(4): 310-316